Does Omental Plugging Provide a Better Surgical Treatment Outcome than the Omentopexy Technique in the Management of Giant Peptic Ulcer Perforation? A Meta-analysis of Comparative Studies - Thawatchai Tullavardhana; Anuwat Chartkitchareon (Oman Medical Journal, 2022)
Objectives: Giant perforation (size > 2 cm) is a catastrophic complication of peptic ulcer disease, which is difficult to repair and leads to postoperative leakage and 60% morbidity and 48.2% mortality rates. The objective of this meta-analysis was to compare the postoperative outcomes of omental plugging and omentopexy in the treatment of giant ulcer perforation. Methods: The dataset was defined by searching for articles published until December 2020 from PubMed, Embase, Google Scholar, and the Cochrane database. The search terms included were giant peptic ulcer, peptic ulcer perforation, omentopexy, and omental plug. The data analysis included a study published in English that evaluated the surgical outcomes of omental plugging and omentopexy in the management of giant peptic ulcer perforation patients. Meta-analysis was performed using Review Manager software version 5.4.1. Results: A total of 175 articles were identified during the initial search. After review, eight articles were suitable for inclusion in the meta-analysis. A total of 367 patients were included in the final analysis. The findings demonstrate that when compared to the omentopexy group, the omental plugging technique significantly reduced overall postoperative complications (odds ratio (OR) = 0.29, 95% CI: 0.18–0.47, p =0.0001) and bile leakage rate (OR = 0.18, 95% CI: 0.07–0.46, p =0.0003), resulting in a significantly lower postoperative mortality rate (OR = 0.35, 95% CI: 0.17–0.69, p =0.003). However, there was no significant difference in intraabdominal collection, respiratory tract, and wound infection rates between each surgical treatment group. Conclusions: Omental plugging is a simple surgical procedure associated with fewer postoperative complications and mortality than omentopexy. This technique is a safe surgical treatment option for peptic ulcer perforations > 2 cm.